2006
DOI: 10.2151/jmsj.84.259
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Cyclone Climatology in a Global-Warming Climate as Simulated in a 20 km-Mesh Global Atmospheric Model: Frequency and Wind Intensity Analyses

Abstract: Possible changes in the tropical cyclones in a future, greenhouse-warmed climate are investigated using a 20 km-mesh, high-resolution, global atmospheric model of MRI/JMA, with the analyses focused on the evaluation of the frequency and wind intensity. Two types of 10-year climate experiments are conducted. One is a present-day climate experiment, and the other is a greenhouse-warmed climate experiment, with a forcing of higher sea surface temperature and increased greenhouse-gas concentration. A comparison of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
403
3
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 509 publications
(449 citation statements)
references
References 34 publications
33
403
3
2
Order By: Relevance
“…Oouchi et al (2006) found a general increase in the most intense hurricanes and a decrease in weaker ones for a time-slice simulation forced by current and future surface temperatures and greenhouse gases; similar findings were made by Bengtsson et al (2007). Bender et al (2010) examined the potential climate changes in North Atlantic hurricanes using two versions of the GFDL hurricane model as a downscaling tool applied to tropical cyclones generated in the GFDL climate model.…”
Section: Comparison With Model Simulationssupporting
confidence: 59%
“…Oouchi et al (2006) found a general increase in the most intense hurricanes and a decrease in weaker ones for a time-slice simulation forced by current and future surface temperatures and greenhouse gases; similar findings were made by Bengtsson et al (2007). Bender et al (2010) examined the potential climate changes in North Atlantic hurricanes using two versions of the GFDL hurricane model as a downscaling tool applied to tropical cyclones generated in the GFDL climate model.…”
Section: Comparison With Model Simulationssupporting
confidence: 59%
“…The location of the tropical cyclone MAWAR in the observations is derived from the JMA best track data. Detection of the tropical cyclone in the simulations is based on the criteria shown in Oouchi et al (2006). In the observation (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…There is still an uncertainty about the future changes in tropical cyclone frequency and intensity [Oouchi et al, 2006;Yoshimura et al, 2006;Bengtsson et al, 2006]. Coarse resolution GCMs are not able to represent typical inner structures of tropical cyclones which results in underestimation of intensities [e.g., Krishnamurti et al, 1989;Camargo and Sobel, 2004].…”
Section: Predicted Future Changes In Cyclone Frequency and Intensitymentioning
confidence: 99%
“…Coarse resolution GCMs are not able to represent typical inner structures of tropical cyclones which results in underestimation of intensities [e.g., Krishnamurti et al, 1989;Camargo and Sobel, 2004]. Thus the predictions of Oouchi et al [2006], which were obtained with a 20 km resolution GCM may be more reliable. However, it is to be noted that the simulation time period was limited to 10 a for both present-day and future conditions.…”
Section: Predicted Future Changes In Cyclone Frequency and Intensitymentioning
confidence: 99%
See 1 more Smart Citation